Odpowiedzi

2009-12-01T18:35:48+01:00
A) (m+n)(m-2)+(m-n)(m+1)= m²-2m+nm-2n+m²+m-nm-n= 2m²-m-3n
b)(3x-2)(3x-2y+1)-4x(2x-3y+1)= 9x²-6xy+3x-6x+4y-2-8x²+12xy-4x=x²-7x+4y+6xy-2
c)3(m+1)(n-2)+2(n+1)(m-2)=3(mn-2m+n-2)+2(nm-2n+m-2)=3mn-6m+3n-6+2mn-4n+2m-4=5mn-4m-n-10
d)x(x+1)(x+2)-x(x-1)(x-2)=x(x²+2x+x+2)-x(x²-2x-x+2)= x³+2x²+x²+2x-x³+2x²+x²-2x= 6x²
2009-12-01T18:41:46+01:00
A) ( m+n)(m-2)+(m-n)(m+1)=m2- 2m+ mn- 2n+ m2+ m- mn- n=m-3n
b) (3x-2)(3x-2y+1)-4x(2x-3y+1)=9x2- 6xy+3x-6x+4y-2-8x2+ 12xy-4x=x2- 6xy- 7x+ 4y-2
c) 3(m+1)(n-2) + 2(n+1)(m-2)=3(mn-2m+n-2)+2(mn-2n+m-2)=
=3mn-6m+3n-6+2mn-4n+2m-4=5mn-4m-n-10